2010
DOI: 10.1159/000317342
|View full text |Cite
|
Sign up to set email alerts
|

Nonbacterial Thrombotic (Marantic) Endocarditis in a Patient with Colorectal Cancer

Abstract: Background: Marantic endocarditis, presently termed nonbacterial thrombotic endocarditis (NBTE), is an infrequent post-mortem diagnosis in the adult population but a not so rare event in the course of neoplastic conditions. Case Report: We describe the case of a 74-year-old woman with advanced sigmoid adenocarcinoma, who developed aseptic vegetations in the right atrium of the heart. Systemic anticoagulation therapy was started, and upon clinical improvement systemic chemotherapy was added, resulting in partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…NBTE is another mechanism underlying arterial thromboembolism encountered in patients with neoplastic diseases (3). NBTE is associated with many types of primary carcinomas, with lung, pancreatic and ovarian adenocarcinomas being the most frequently observed (6). An echocardiographic study of 200 living patients with various cancers found evidence of NBTE in approximately 19% of the patients, and evidence of NBTE was 10-fold higher in these patients than in a control group (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NBTE is another mechanism underlying arterial thromboembolism encountered in patients with neoplastic diseases (3). NBTE is associated with many types of primary carcinomas, with lung, pancreatic and ovarian adenocarcinomas being the most frequently observed (6). An echocardiographic study of 200 living patients with various cancers found evidence of NBTE in approximately 19% of the patients, and evidence of NBTE was 10-fold higher in these patients than in a control group (7).…”
Section: Discussionmentioning
confidence: 99%
“…However, she exhibited no neurological deficits. The pathogenesis of NBTE in patients with malignancy remains partially elusive, although it is intimately related to cancer-associated thrombophilia, originally described as Trousseau syndrome (2,6). In the presence of excessive clotting factor activity, endothelial damage caused by circulating cytokines, such as tumor necrosis factor and interleukin-1, can trigger platelet deposition in areas of high blood flow (2,5,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Left sided and bilateral vegetations are more consistent with marantic endocarditis than with the other major cause of vegetations, infective endocarditis. 8 Unlike marantic endocarditis, infective endocarditis is an infection of the endocardium which is frequently caused by bacteria such as Staphylococcus aureus and Streptococcus viridans, and occasionally fungi. The organisms induce platelet aggregation and activate the clotting cascade, leading to the deposition of fibrin and bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a history of cardiac murmurs, which are characteristic of infective endocarditis, is often absent in marantic endocarditis. 8 Haematological and coagulation studies may have been normal but unexpected results should raise the suspicion of marantic endocarditis, especially when infective causes have been ruled out by negative blood cultures, or by a poor response to antibiotic therapy. 8 McKay and Wahler developed a triad to assist in diagnosing marantic endocarditis which consists of a history of a disease known to be associated with marantic endocarditis, a documented heart murmur, and a history of multiple systemic emboli.…”
Section: Discussionmentioning
confidence: 99%